The Use of Force against Ukraine and International Law Jus Ad Bellum, Jus In Bello, Jus Post Bellum (T.M.C. Asser Press, 2018)
Written by a team of international lawyers from Europe, Asia, Africa, and the Caribbean, this book analyses some of the most significant aspects of the ongoing armed conflict between the Russian Federation and Ukraine. As challenging as this conflict is for the international legal order, it also offers lessons to be learned by the States concerned, and by other States alike. The book analyses the application of international law in this conflict, and suggests ways for this law's progressive development. It will be useful to practitioners of international law working at national Ministries of Defence, Justice, and Foreign Affairs, as well as in Parliaments, to lawyers of international organizations, and to national and international judges dealing with matters of public international law, international humanitarian law and criminal law. It will also be of interest to scholars and students of international law, and to historians of international relations. Sergey Sayapin is Assistant Professor in International and Criminal Law at the School of Law of the KIMEP University in Almaty, Kazakhstan. Evhen Tsybulenko is Professor of Law at the Department of Law of the Tallinn University of Technology in Tallinn, Estonia.